Emerging Asia's Impact on Australian Growth : Some Insights From GEM - Hunt, Benjamin (IMF Working Papers; Working Paper ;, 2010)
Over the last decade, GDP growth in emerging Asia was roughly twice as fast as average world growth. The IMF's Global Economy Model (GEM) is used to estimate the impact that emerging Asia's growth differential has had on Australia. The simulation analysis, which replicates some key features from the last decade, suggests that roughly 25 percent of Australia's growth over the last decade has been from emerging Asia's growth differential over that period. Looking ahead, the analysis suggests that should emerging Asia continue to grow in a similar fashion, Australia's growth dividend could almost double. On the other hand, if growth in emerging Asia remained strong, but became more balanced across the tradable and nontradable goods sectors then Australia's growth dividend would be slightly lower than the estimate for the last decade.